Можливі проблеми зняття з експлуатації АЕС України - Safonov V.A.; Kuchinsky V.K.; Gavrish V.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2003)
An information about exploitation dates of nuclear power plants in Ukraine is presented. An analysis of variants of works on their removal from exploitation is given and the main thing measures securing their implementation in the conditions of Ukraine are definite.